Henriette Sontag - Winterhalter, Franz Xaver, 1805-1875 (artist):::Creator:::::::::::: (Verlag v. Baumgärtner's Buchh.; Leipzig; Germany)
Engraving of Henriette Sontag by an unknown artist based on the painting by Franz Xaver Winterhalter.